Global tuberculosis report 2017 / Autores Laura Anderson, Annabel Baddeley, Anna Dean, Hannah Monica Días, Dennis Falzob, Katherine Floyd, Inés García Baena, Nebiat Gebreselassie, Christopher Gilpin, Philippe Glaziou,Yohhei Hamada, Avinash Kanchar,Irwin Law, Christian Lienhardt, Andrew Soroka,Charalambos Sismanidis, Hazim Timimi, Wayne Van Gemert, Diana Weil y Matteo Zignol - Anderson, Laura (World Health Organization, 2017)
The designations empoyed and the presentation of the material in this publication do no imply the expression of any opinion whatsoever on the part of WHO concerning the legal status of any country, territory, city or area or of its authorities, or concening the delimitation of its frontiers or boundaires